New insights in ferroptosis: Potential therapeutic targets for the treatment of ischemic stroke - Wei, Ziqing; Xie, Yi; Wei, Mingze; Zhao, Huijuan; Ren, Kaidi; Feng, Qi; Xu, Yuming (Frontiers in Pharmacology, 2022)
Stroke is a common disease in clinical practice, which seriously endangers people's physical and mental health. The neurovascular unit (NVU) plays a key role in the occurrence and development of ischemic stroke. Different from other classical types of cell death such as apoptosis, necrosis, autophagy, and pyroptosis, ferroptosis is an iron-dependent lipid peroxidation-driven new form of cell death. Interestingly, the function of NVU and stroke development can be regulated by activating or inhibiting ferroptosis. This review systematically describes the NVU in ischemic stroke, provides a comprehensive overview of the regulatory mechanisms and key regulators of ferroptosis, and uncovers the role of ferroptosis in the NVU and the progression of ischemic stroke. We further discuss the latest progress in the intervention of ferroptosis as a therapeutic target for ischemic stroke and summarize the research progress and regulatory mechanism of ferroptosis inhibitors on stroke. In conclusion, ferroptosis, as a new form of cell death, plays a key role in ischemic stroke and is expected to become a new therapeutic target for this disease.